Natural polymers as alternative adsorbents and treatment agents for water remediation - Diego Gomez-Maldonado; Iris B. Vega Erramuspe; Maria S. Peresin (BioResources)
This review examines the roles of different natural polymers, composites, and nanoengineered materials that have been studied in the last 10 years for their use in water treatment. As water quality is a global concern, the use of natural and sustainable materials is fundamental to obtain high value products that can remediate water systems without generating other pollution sources or require extra energy inputs or high side costs. Filtration systems often can provide an ideal alternative to conventional water treatment. Herein the attention is focused on polysaccharides, as these can be easily obtained from green processes and can be sourced from what nowadays are considered as agricultural waste. The inherent variety of functional groups that they have provides a better interaction with certain types of pollutants. Thus, biomaterials have been harnessed to generate filtration systems and other water treatment options.